The size of endotracheal tube and sore throat after surgery: a systematic review and meta-analysis. - Baoji Hu; Rui Bao; Xiaolin Wang; Shanshan Liu; Tianzhu Tao; Qun Xie; Xiongwei Yu; Jinbao Li; Lulong Bo; Xiaoming Deng (PLoS ONE)
Background Recent studies showed that sore throat following endotracheal intubation was a common problem following surgery. The objective of this systematic review and meta-analysis of published randomized controlled trials (RCTs) or cohort studies was to estimate whether the size of endotracheal tube (ETT) affects the incidence of postoperative sore throat (POST) after general anesthesia. Methods The following databases were searched electronically: PubMed (updated to Dec 2012), EMBASE (updated to 15 Dec 2012), Google scholar, World Health Organization International Clinical Trials Registry Platform (Jul 2011), Chinese BioMedical Literature Database (1978 to Jul 2011), and China National Knowledge Infrastructure (1994 to Jul 2011). Studies comparing the size of endotracheal tube for elective surgery were included. Results Three trials with a total of 509 female patients were included in the current analysis. The size of ETT used were 6.0 mm and 7.0 mm. Pooled studies from these trials showed that the smaller size of ETT (6.0 mm) significantly decreased the incidence of POST in post-anesthesia care unit (PACU) (RR = 0.56, 95% CI 0.42-0.75, P<0.01) and at 24 h after surgery (RR = 0.69, 95% CI 0.48-0.99, P<0.05). A smaller size of ETT (6.0 mm) was associated with a lower incidence of PH in PACU (RR = 0.69, 95% CI 0.55-0.87, P<0.01), but did not affect the incidence of PH at 24 h after surgery (RR = 0.73, 95% CI 0.46-1.15, P>0.05). Conclusion Our meta-analysis suggests that patients under general anesthesia with a smaller size of ETT (6.0 mm) were associated with a lower incidence of POST in female patients. More studies with adequate numbers of patients were warranted to evaluate other size of ETT on the incidence of PH and POST after general surgery among different populations.